The crystal structure of N′1,N′3-bis((E)-thiophen-2-ylmethylene)isophthalohydrazide monohydrate, C18H16N4O3S2 - Yin Zi-Yi; Zou Fei; Chen Jue-Yuan; Yuan Lin; Li Zhong-Yan (Zeitschrift für Kristallographie - New Crystal Structures)
C18H16N4O3S2, monoclinic, C2/c (no. 15), a = 19.694(4) Å, b = 11.450(2) Å, c = 8.3382(16) Å, β = 91.820(2)∘ $91.820{(2)}^{° }$ , V = 1879.3(6) Å3, Z = 4, Rgt ${R}_{gt}$ (F) = 0.0408, wRref $wR_{ref}$ (F 2) = 0.1206, T = 296(2) K.